PENINGKATAN KEMAMPUAN MASYARAKAT DALAM PERAWATAN DAN PENCEGAHAN DAMPAK TEKANAN DARAH TINGGI DI RT. 37 KELURAHAN SEI PANGERAN KECAMATAN ILIR TIMUR I PALEMBANG - Sulaiman, Sulaiman; Lukman, Lukman; Mediarti, Devi; Pastari, Marta (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2020)
Hypertension or high blood pressure is a cause of death and high morbidity. A history of hypertension along with an unhealthy lifestyle such as tobacco consumption, high fat consumption, lack of fiber, excess salt consumption, lack of exercise, alcoholism, obesity, high blood fat and stress, will exacerbate the risk of complications such as myocardial infarction, stroke. , kidney failure, and sometimes even cause sudden death.To improve the community's capacity, efforts need to be made, one of which is health education. Health education aims to provide participants with the ability to treat hypertension and prevent side effects or complications that can arise. Education using this health education method will involve residents in the RT. 37 Kelurahan Sei Pangeran, Ilir Timur I Subdistrict, Palembang in 2016. The expected results in this education are participants are able to explain how to treat and prevent high blood pressure.